Single coronary artery anomaly causing ischemic mitral insufficiency. - Ay, Yasin; Aydın, Cemalettin; Ay, Nuray Kahraman; Inan, Bekir; Başel, Halil; Zeybek, Rahmi (My University, 2014)
Single coronary artery anomaly is rarely seen, and although it can present with sudden death, chest pain, arrhythmia, myocardial infarction, or congestive heart failure, it can also be asymptomatic. We describe the case of a 58-year-old man with single coronary artery anomaly in whom the coronary artery stemmed from the left coronary sinus and caused ischemic mitral insufficiency due to left anterior descending artery stenosis. He underwent successful mitral valve repair and coronary bypass.
Keywords: Cardiac valve annuloplasty; Coronary artery bypass; Coronary vessel anomalies; Mitral valve insufficiency